Percutaneous Laser Lumbar Disc Decompression - Salami, Sunday Onimisi; Osholowu, Adedayo Gbolahan; Oyeniran, David Anuoluwapo (Nigerian Journal of Orthopaedics and Trauma, 2018)
Acute or chronic back and neck pain is a major social, economic and healthcare issue in all communities. Nearly 80% of the population experiences backache during their lifetime. Percutaneous laser disc decompression (PLDD) is one of the minimally invasive methods for treating low back pain. There have been numerous reports of its use since the first case in 1986, and the indications are expanding daily. We present a case of a 38‑year‑old banker with chronic prolapsed intervertebral disc who had 7‑year history of recurrent low back pain from prolapsed L4–L5 intervertebral disc with radiculopathy. She had PLDD procedure in our clinic under local anaesthesia as day case. After the procedure, the patient was observed for 4 h and discharged home. She felt significant pain relief after the operation and was placed on a lumbar corset for a week. The pre‑surgery assessment using Oswestry Low Back Pain Disability Index was 58% (severe disability) but was reduced to 26.7% (moderate disability) after 3‑month post‑surgery follow‑up. At 12‑month follow‑up, the Oswestry score was 16% and the patient outcome was good according to MacNab’s criteria. PLDD is safe and effective for the treatment of low back pain seen in the post‑operative result of this presented case.